Fracture properties of OPC included ambient cured geopolymer concrete by size effect method. Issue 1 (June 2020) - Sabu, N J; Thomas, Job
Abstract: This paper presents the details of experimental study on the fracture properties of high strength geopolymer concrete. The geopolymer concrete prepared in this study was cured in ambient temperature. This was achieved by adding small amount of OPC in the mixture. A total of 42 notched beam specimens with varying span to depth ratio (l/d) between 8 and 6 and notch depth to total depth ratio (a0 /d) between 0.2 and 0.4 was cast. All beam specimens were tested under three point bending test. The fracture properties, namely, fracture energy (Gf ), critical stress intensity factor (KIc ), process zone length (cf ), and crack tip opening displacement corresponding to peak load (δc ) were determined by size effect law (SEL). The results show that the fracture properties of ambient cured geopolymer concrete are comparable with that of ordinary concrete of same strength.